2020
DOI: 10.1145/3341197
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Dyslexic Students’ Motivation for Enhanced Learning in E-learning Systems

Abstract: E-Learning systems can support real-time monitoring of learners' learning desires and effects, thus offering opportunities for enhanced personalized learning. Recognition of the determinants of dyslexic users' motivation to use e-learning systems is important to help developers improve the design of e-learning systems and educators direct their efforts to relevant factors to enhance dyslexic students' motivation. Existing research has rarely attempted to model dyslexic users' motivation in e-learning context f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…They found that factors like the timeliness and availability of information significantly contribute to e-learning user satisfaction. Elearning users tend to be more satisfied when they access current and well-available information [78], [79].…”
Section: Hypothesis Test Resultsmentioning
confidence: 99%
“…They found that factors like the timeliness and availability of information significantly contribute to e-learning user satisfaction. Elearning users tend to be more satisfied when they access current and well-available information [78], [79].…”
Section: Hypothesis Test Resultsmentioning
confidence: 99%